Immunomodulation of NK, NKT and B/T cell subtypes in relapsed/refractory multiple myeloma patients treated with pomalidomide along with velcade and dexamethasone and its association with improved progression-free survival - Prabhala, Rao; Pierceall, William E.; Samur, Mehmet; Potluri, Lakshmi B.; Hong, Kevin; Peluso, Teresa; Talluri, Srikanth; Wang, Angela; Katiki, Aishwarya; Vangala, Sahan D.; Buonopane, Michael; Bade, Vaishnavi; et al. (Frontiers in Oncology, 2023)
Background: Multiple Myeloma (MM) patients exhibit dysregulated immune system, which is further weakened by chemotherapeutic agents. While cereblon-modulating agents, such as pomalidomide and lenalidomide, have been found to improve the immune profile, the efficacy of their impact in combination with other treatments is yet unknown. Methods: We conducted an immune-profiling of a longitudinal cohort of 366 peripheral blood samples from the CC4047-MM-007 (OPTIMISMM, NCT01734928)1 study. This study followed relapsed/refractory Multiple Myeloma (RRMM) patients who were treated with Velcade + dexamethasone (Vd), or Vd with pomalidomide (PVd). 366 blood samples from 186 patients were evaluated using multi-color flow cytometry at 3 timepoints: screening, cycle 1, and cycle 3. Results: Among NK and NKT cell populations, adding pomalidomide showed no inhibition in the frequency of NK cells. When expression of double positivity for activation markers like, p46/NKG2D, on NK cells was higher than the median, PVd treated patients showed significantly better (p=0.05) progression-free survival (PFS) (additional 15 months) than patients with lower than the median expression of p46/NKG2D on NK cells. PVd treated patients who expressed CD158a/b below the median at cycle 1 demonstrated a significantly better PFS (more than 18months). Among B cell subtypes, PVd treatment significantly increased the abundance of B1b cells (p<0.05) and decreased Bregs (p<0.05) at cycle 1 and cycle 3 when compared to screening samples. Of all the B cell-markers evaluated among paired samples, a higher expression of MZB cells at day 8 of cycle 1 has resulted in enhanced PFS in PVd treated patients. Within T cells, pomalidomide treatment did not decrease the frequency of CD8 T cells when compared with screening samples. The higher the surface expression of OX-40 on CD8 T cells and the lower the expression of PD-1 and CD25 on CD4 T cells by PVd treatment resulted in improved PFS. Conclusions: The prognostic significance for the number of immune markers is only seen in the PVd arm and none of these immune markers exhibit prognostic values in the Vd arm. This study demonstrates the importance of the immunomodulatory effects and the therapeutic benefit of adding pomalidomide to Vd treatment.